Clinical significance of the cribriform pattern in invasive adenocarcinoma of the lung. Issue 10 (28th June 2019) - Zhang, Ruizhen; Hu, Guiming; Qiu, Jinhuan; Wu, Huifang; Fu, Wenjing; Feng, Yikun; Zhang, Min; Chen, Chen; Sun, Jianping; Zhang, Yan; Ren, Jingli
Abstract : Purpose: According to the WHO, the cribriform pattern is a subtype of acinar (Aci) predominance in invasive adenocarcinoma (ADC) of the lung. Recently, several studies have demonstrated poor prognosis in patients with cribriform predominance. This study was performed to examine the correlations of cribriform pattern with the clinicopathology, molecular features and prognosis in patients with invasive ADC. Methods: Histological subtypes were evaluated in 279 patients who underwent complete resection for invasive ADC. Patients of the Aci-predominant subtype were divided into two subgroups according to the percentage of cribriform cancer (≥5% vs <5%). Clinicopathological characteristics, overall survival (OS), disease-free survival (DFS) and molecular changes were compared. In addition, both OS and DFS were compared between patients with cribriform-predominant (n=33) and pure Aci-predominant (n=88) ADCs. Results: A cribriform pattern was found in 111 (39.8%) cases and ranged from 5 % to 100 % of the total tumour volume (mean±SEM, 30%±2%). Of 117 patients with Aci predominance, 79 showed the cribriform pattern, while the remaining 38 did not. The cribriform pattern was associated with aggressive pathological behaviour, including advanced stages of cancer, nuclear atypia, mitoses, lymph node invasion, metastasis and larger tumour size. The subgroup with cribriform cancer (≥5%) had significantly poorer OS and DFS compared with the cribriform-negative (<5%) group. In addition, Cox multivariate analyses revealed that the cribriform pattern was an independent predictor of OS but not DFS. Moreover, OS was significantly lower in the cribriform-predominant group than in the Aci-predominant group. Conclusion: The cribriform pattern is associated with aggressive pathological behaviour and is an independent poor prognostic indicator in patients with Aci-predominant ADC of the lung.